2021
DOI: 10.1155/2021/6689597
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation on Heat Transfer Characteristics of Steam Condensation in Presence of Noncondensable Gas under Natural Convection

Abstract: The NHR-200 reactor in China adopts the noncondensable gas self-stabilizing control and the noncondensable gas used for pressure stabilization control can weaken steam condensation heat transfer in the integrated steam-gas pressurizer. A condensation experimental system was established and the heat transfer characteristics of steam-nitrogen and steam-argon condensation under natural convection had been investigated. The pressure ranged from 0.516 to 5.10 MPa. The distributions of nitrogen and argon in the stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…As the mixture condenses, it becomes denser (air and nitrogen are heavier than steam) and moves downward. In a study conducted by Ma et al [94], steam condensation was examined within a pressure range spanning from 0.516 to 5.10 MPa while considering a broad spectrum of nitrogen mass fractions, ranging from 5% to 85%. The results indicated that the condensation HTC decreased from 1.393 to 0.165 kW/ (m 2 •K) at a pressure of 0.517 MPa, and nitrogen mass fractions ranged from 9.03% to 75.76%.…”
Section: Ncg Sources and Their Transport Perspective In Nppsmentioning
confidence: 99%
“…As the mixture condenses, it becomes denser (air and nitrogen are heavier than steam) and moves downward. In a study conducted by Ma et al [94], steam condensation was examined within a pressure range spanning from 0.516 to 5.10 MPa while considering a broad spectrum of nitrogen mass fractions, ranging from 5% to 85%. The results indicated that the condensation HTC decreased from 1.393 to 0.165 kW/ (m 2 •K) at a pressure of 0.517 MPa, and nitrogen mass fractions ranged from 9.03% to 75.76%.…”
Section: Ncg Sources and Their Transport Perspective In Nppsmentioning
confidence: 99%